1982
DOI: 10.1177/30.4.6174568
|View full text |Cite
|
Sign up to set email alerts
|

Fibronectin involvement in granulation tissue and wound healing in rabbits.

Abstract: This study describes the distribution of fibronectin and its association with reticulin fibers (type III collagen) and hyaluronic acid in shallow rabbit wounds. Linear incisions were made dorsally with a surgical blade. Animals were sacrificed and 1 , 2, 3, 4, 5, and 8 day wounds were examined using peroxidase-antiperoxidase to localize affinity-punfied antibodies to fibronectin. Tissue samples were also stained with hematoxylin and eosin in addition to silver stains for reticulin, and Alcian blue for hyaluron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
36
0

Year Published

1984
1984
1996
1996

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(39 citation statements)
references
References 27 publications
3
36
0
Order By: Relevance
“…Repesh and co-workers [31] described an intense fibronectin staining in 8-day-old granulation tissue in rabbits which could also be detected by us in granulation tissue of skin wounds with an age of less than 17 days, especially less than 3 weeks.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…Repesh and co-workers [31] described an intense fibronectin staining in 8-day-old granulation tissue in rabbits which could also be detected by us in granulation tissue of skin wounds with an age of less than 17 days, especially less than 3 weeks.…”
Section: Discussionsupporting
confidence: 72%
“…Clark and co-workers [7] investigated the role of fibronectin during neoangiogenesis in granulation tissue and reported a reduction of this glycoprotein in the capillary wall with decreasing capillary ingrowth. Repesh et al [31] found fibronectin in the fibrin clot and described an intense reaction in 8-day-old granulation tissue from rabbits. Viljanto et al [37] detected fibronectin at the margin of cellulose compresses in 3-hour-old surgical wounds.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Fibronectin has been proposed as a mediator of granulation tissue formation and wound healing (Repesh et al, 1982). The staining of vascular basement membrane in the tumours is also consistent with that in wound healing (Clark et al, 1982) and the possibility that the stroma of tumours is the same type of tissue as that of a healing wound should be considered, a concept which has been suggested in the case of breast cancer (Dvorak et al, 1981).…”
Section: Discussionmentioning
confidence: 97%
“…Increased levels of plasma fibronectin under acute phase conditions might facilitate the removal of microaggregates, bacteria, and soluble debris from the circulation and, thus improve the function of the reticulo-endothelial System (56,57). Furthermore, acute phase fibronectin might be deposited in the tissue at sites of acute inflammation and injury and thereby support wound healing and tissue repair (58,59). Stimulated synthesis of fibronectin in hepatocytes would therefore compensate for its increased consumption under these conditions.…”
Section: Discussionmentioning
confidence: 99%